2022
DOI: 10.3390/cancers14235774
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Union after Jaw Reconstruction with Fibula-Free Flap: Conventional vs. CAD/CAM Patient-Specific Implants

Abstract: This is a monocentric, retrospective study of patients who underwent successful immediate or delayed maxilla or mandible reconstructions with FFF from January 2005 to December 2021. Panoramic radiograph, computed tomography scans, and cone-beam CTs were analyzed concerning the osseous union of the intersegmental junctions between maxillary or mandibular native jaw and fibular bone. The primary parameter was to estimate the status of osseous union according to osteosynthesis type. A total number of 133 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
1
13
4
Order By: Relevance
“…In a comparison of FHS and VSP with customized patient specific implants for mandibular reconstruction with fibular free flap, Knitschke et al observed slightly earlier complete bony union in patients in the patient-specific implants group than in patients in the FHS group. 20 However, in contrary to our results, the rate of incomplete bony union was significantly higher in the patient-specific implant group. 20 There are several proposed explanations for the difference in union rates.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In a comparison of FHS and VSP with customized patient specific implants for mandibular reconstruction with fibular free flap, Knitschke et al observed slightly earlier complete bony union in patients in the patient-specific implants group than in patients in the FHS group. 20 However, in contrary to our results, the rate of incomplete bony union was significantly higher in the patient-specific implant group. 20 There are several proposed explanations for the difference in union rates.…”
Section: Discussioncontrasting
confidence: 99%
“…6,7,[14][15][16] While several studies have reported on the bony union status of maxillary and mandibular reconstruction, 4,12,[17][18][19] fewer compare this outcome between VSP and FHS. 11,16,20 To the best of our knowledge, our study is the first comparing the rate of union in FHS and VSP in patients undergoing either mandible or maxilla reconstruction with either fibular or scapular free-flap. By including both sites of reconstruction and origins of free-flap, we were able to demonstrate that these variables had no significant effect on the rate of union.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Intersegmental volumes and gap widths are critical in this regard, and we were able to show that they were significantly smaller in the commercial planning group compared to the in‐house planning group. Knitschke and colleagues confirmed this finding for intersegmental volumes and observed earlier ossification of the segments, which is critical for adequate graft healing 26 . Tran et al also measured smaller gaps in a commercial planning solution that integrated PSIs 27 .…”
Section: Discussionmentioning
confidence: 87%
“…Knitschke and colleagues confirmed this finding for intersegmental volumes and observed earlier ossification of the segments, which is critical for adequate graft healing. 26 Tran et al also measured smaller gaps in a commercial planning solution that integrated PSIs. 27 Compared to the in-house solution, the commercial planning solution offers the advantage of virtually modeling and fabricating a PSI in a laser sintering or milling process that precisely fits the patient's reconstructed mandible.…”
Section: Discussionmentioning
confidence: 99%